The Mystery of “those icy climes” (Shelley 269): Literature, Science and Early Nineteenth-century Polar Exploration - Catherine Lanone (Cahiers Victoriens et Edouardiens)
Nineteenth-century science probed into the mystery of ice, from the structure of snowflakes to glaciers to Polar exploration. Literature reflects this attempt to understand the shifting nature of ice, a transparent yet deceptive—neither liquid nor truly solid—elemental structure. While glaciers become the sublime site of Romantic poetic epiphany, Mary Shelley subverts the euphoric associations of pristine settings by choosing to locate a crucial confrontation between creature and creator in the Alps, then by opting for Walton’s search for the North Pole and the Northwest Passage as a frame for Victor’s narrative. Walton’s delusion and search for an open sea ties in with the journals of contemporary expeditions, as if Mary Shelley had sensed that the jingoistic expeditions might turn into epic disasters. The loss of Franklin’s last expedition triggered an unprecedented series of rescue expeditions which allowed to map unknown areas yet also proved how shifting and unconquerable the ice remained for nineteenth-century boats.